ANALISIS VARIASI JUMLAH SUDU BERENGSEL TERHADAP UNJUK KERJA TURBIN CROSS FLOW ZERO HEAD - Padang, Yesung Allo; Okariawan, IDK; Wati, Mundara (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2014)
Micro Hydro Powewr Plant (MHPP) is a power plant that converts water energy into electrical in a small capacity. Developing MHPP means developing renewable energy which is environmentally save. In this researh the position of cross flow turbine is submerged in water so it is said cross flow zero head turbine. The purpose of this reserch is to analyze the performances of cross flow zero head turbne. The variation parameters include number of blade (12, 6 and 4 blades), fixed blades and sliding blades (unbolted blades). The turbine performances to be analyzed are system efficiency, turbine output power and generator speed. The results show that the best turbine performance is obtained when number of blades is 12 with fixed blade. This yields to the best system efficiency of 0.47% obtained at generator speed of 89.9 rpm and generator power output of 29.25 Watts.